Dimensi Desentralisasi Analisa Pola Hubungan Kewenangan Dalam Pengelolaan Pertambangan - rahmat robuwan; Wirazilmustaan Wirazilmustaan (Fakultas Hukum Universitas Bangka Belitung, 2021)
This research is motivated by the implementation of decentralization in a country that cannot be separated from mineral resources owned by each region. The arrangements of management of mining become an inseparable part in the editorial discussion of the policy directions and thw arrangements of regarding decentralization. The Regions that have the potential for explorative natural resources are faced with a complicated situation and full of pros and cons when discussing about mining in their area. The revised of the act of regional government certainly contributes to the political of decentralized law and the arranggement of mining. The relationship between the central government and regional governments, especially the provinces in mining management based on the Act of Mineral and Coal must receive special attention, because it has a direct orientation towards the perspective of decentralization. To discuss these issues, conducted by normative legal research method with the statute approach. The authority of the central government in managing mineral and coal mining has a paradigm of decentralization that is felt to be getting stronger. Exceptions to government affairs which by acts are determined as central government affairs are the constitutional basis of legislators as the basis for decentralization